Association of variants in CDKN2A/2B and CDKAL1 genes with gestational insulin sensitivity and disposition in pregnant Han Chinese women. Issue 3 (7th January 2015) - Mei, Jie; Liao, Shunyao; Liu, Yunqiang; Tan, Yuande; Wang, Hailian; Liang, Yaming; Dong, Xianjue; Song, Wenzhong; Gan, Lu; Deng, Shaoping
Abstract: Aims/Introduction: Variants in cell cycle regulation genes, CDKAL1 and CDKN2A/2B, have been suggested to be associated with type 2 diabetes, and also play a role in insulin procession in non‐diabetic European individuals. Rs7754580 in CDKAL1 and rs7020996 in CDKN2A/2B were found to be associated with gestational diabetes in Chinese individuals. In order to understand the metabolism mechanism of greatly upregulated maternal insulin signaling during pregnancy and the pathogenesis of gestational diabetes, we investigated the impact of rs7754580 and rs7020996 on gestational insulin regulation and procession. Materials and Methods: We recruited 1, 146 unrelated, non‐diabetic, pregnant Han Chinese women (age 28.5 ± 4.1 years, body mass index 21.4 ± 2.6 kg/m 2 ), and gave them oral glucose tolerance tests. The indices of insulin sensitivity, insulin disposition, insulin release and proinsulin to insulin conversion were calculated. Rs7754580 in the CDKAL1 gene and rs7020996 in the CDKN2A/2B gene were genotyped. Under an additive model, we analyzed the associations between the variants and gestational insulin indices using logistic regression. Results: By adjusting for maternal age, body mass index and the related interactions, CDKAL1 rs7754580 risk allele C was detected to be associated with increased insulin sensitivity ( P = 0.011), decreased insulin disposition ( P = 0.0002) and 2‐h proinsulin conversion ( P = 0.017). CDKN2A/2B rs7020996 risk allele T was found to be related to decreased insulin sensitivity ( P = 0.002) and increased insulin disposition ( P = 0.0001). Conclusions: The study showed that cell cycle regulating genes might have a distinctive effect on gestational insulin sensitivity, β‐cell function and proinsulin conversion in pregnant Han Chinese women. Abstract : We analyzed the associations between the variants in Cell cycle regulation genes and gestational insulin indices using logistic regression. The study showed that cell cycle regulating genes might have distinctive effect on gestational insulin sensitivity, beta‐cell function and proinsulin conversion in pregnant Han Chinese women.